Importancia de las aguadas para el pecarí de labios blancos (Tayassu pecari) en la Selva Maya, Guatemala - Moreira-Ramírez, José Fernando; Reyna-Hurtado, Rafael; Hidalgo-Mihart, Mircea; Naranjo, Eduardo; Ribeiro, Milton C. [UNESP]; García-Anleu, Rony; Mérida, Melvin; Ponce-Santzo, Gabriela (Asociacion Mexicana de Mastozoologia, 2016)
Water is considered an essential nutrient for wildlife and, when not in the proper proportion, can be a limiting factor to populations. Differences in water dependency among ungulate species can arise through a variety of physiological, morphological and behavioral mechanisms employed in maintaining the balance of temperature and water. The white-lipped peccary forms large and cohesive groups of 10 to over 300 individuals inhabiting dense tropical forests. Our objectives were to describe the use of waterholes by white-lipped peccaries groups in a humid site of the Selva Maya and evaluate the effect of humidity may have on the visit frequency, group size and activity patterns. From June to August 2014 and February to April 2015 seven waterholes were monitored using digital camera traps. The visit frequency was estimated by dividing the number of events between 1,000 sampling effort traps night. The minimum group size and age structure were estimated for each separate event. Activity patterns were estimated at one-hour intervals for the dry and rainy seasons. Forty-seven and 185 separate events for the rainy and dry season respectively were obtained. The sampling effort in each period was 630 traps night. For the rainy and dry season we obtained a visit frequency of 74.6 and 293.7 respectively. For the rainy and dry season an average group size of 17 (± 9.5) and 25.5 (± 12.6) were estimated respectively. The groups are mainly composed of adults. The presence of newborns was mainly in August and April. Activity patterns were mainly recorded between 10:00 h and 16:00 h. The visit frequency estimated is higher compared to other protected areas in the Selva Maya. The minimum group size estimated is similar to those reported in dry areas within the Selva Maya. The presence of newborns was reported during all months of the study, existing peaks during August, March and April. The white-lipped peccary visited the waterholes mainly during the day between 10:00 h and 16:00 h. Waterholes in the Laguna del Tigre National Park can be called sanctuaries for white-lipped peccaries because are extremely important in the ecology of this social ungulate.
Importance of waterholes for white-lipped peccary (Tayassu pecari) in the Selva Maya, Guatemala
Keywords: Births season; Camera traps; Conservation; Guatemala; Selva maya; Ungulate